Positividad y negatividad del aburrimiento: una hermenéutica de la cotidianidad - Dasuky Quiceno, Samir Ahmed (2023)
This paper considers the positivity and negativity of boredom to understand the horizon in which contemporary society constructs its sense of everyday life. Mymethod follows Heidegger’s interpretative proposal, guided by the concept of everyday life in dialogue with Han, concerning the manifestation of boredom inthe everyday life of individuals. In the first part of this paper, I discuss the determinations of instrumental rationality and neoliberalism in sense-constructionwithin contemporary society. Then, in the second part, I attempt to explain the dialectic impossibility of the positivity of boredom. This leads to understanding how the negativity of boredom enables from dialectics a negation of neoliberal discourse. Understanding this is relevant when positing the negativity of boredom as a world possibility. I conclude that boredom is an openness to the ways in which contemporary society constructs its everyday life.